Effect of Bee Bread on Corticosterone Level in Rat Dams Exposed to Gestational Heat Stress - Nur Akmar Nadhirah Mohd Nor; Asmad Kari; Mohd Nizam Haron; Connie Fay Komilus (Tropical Life Sciences Research, 2023)
Environmental temperature rises are powerful stimuli that can alter both the sympathetic nervous system and the hypothalamic-pituitary-adrenocortical axis (HPA). Heat stress has been shown to harm pregnancy outcomes such as causing spontaneous abortion, low birth weight, growth retardation and stillbirth. Supplementation of bee bread in pregnant rats under heat stress exposure has been shown to improve the pregnancy outcomes. However, whether supplementation of bee bread during heat stress exposure may also reduce the level of the stress hormone, corticosterone has yet been reported. Therefore, this study aims to determine the effect of bee bread on corticosterone level, progesterone level, oestradiol level and zonation of the adrenal cortex of pregnant rats under heat stress exposure. Pregnant rats were randomly categorised into four groups (n = 6): Control (C: standard feeding), Treatment 1 (T1: 0.5 g bee bread/kg body weight/ day), Treatment 2 (T2: standard feeding with heat exposure), and Treatment 3 (T3: 0.5 g bee bread/kg body weight/day with heat exposure). Bee bread (0.5 g/kg body weight/ day) was force-fed to pregnant rats through oral gavage beginning on day 0 of pregnancy and continuing until delivery. Heat stress was generated experimentally by putting both T2 and T3 rats in an egg incubator for 45 min daily at a temperature of 43°C till delivery. On a postnatal Day 21, dams were euthanised to assess serum corticosterone, progesterone, oestradiol levels and adrenal gland histology. Rats in the T2 group had a significantly (P < 0.05) increase in the zona fasciculata thickness (94.95 ± 1.55 ?m) and higher corticosterone levels (49.57 ± 1.57 ng/mL) compared with control. However, supplementation of bee bread during heat stress was able to show an improvement in adrenal zona fasciculata thickness by decreasing to 79.89 ± 3.08 ?m and corticosterone level reduced to 35.31 ± 1.73 ng/mL significantly (P < 0.05). Therefore, these findings may imply that bee bread is effective as a neutralizer in lowering the production of stress hormone.